Leader Humility and Employee Accountability: Psychological Safety as Mediator and Formalization as Moderator - Natria, Deri; Yasmina, Eikla Luwlu; Riantoputra, Corina (Makara Human Behavior Studies in Asia, 2023)
Employee accountability is significant for every organization. Even though leaders are regarded as essential to increasing employee accountability, the mechanism by which leaders influence employee accountability has not yet been researched comprehensively. Employing the social information processing theory, this study argues that leader humility influences employee accountability through psychological safety, and moderated by formalization. Data collection was carried out by convenience sampling using the time-lagged data collection method from 279 employees in a state-owned company in Indonesia. Accountability, leader humility, psychological safety, and formalization scales were used to measure the variables in this study.This model predicted 38% of the variance of employee accountability, and results of analysis using the Hayes' PROCESS Macro Model 14 show: (1) Leader humility relates directly and positively with employee accountability (2) psychological safety mediates the positive relationship between leader humility and employee accountability; (3) the indirect effect of leader humility on employee accountability is strengthened when formalization increases. The result of this study demonstrates that a leader’s character and formalization in the organizations are the keys to build employee accountability.